Inadequacies in Local Entrepreneurial Ecosystems that Impede Growth-Oriented Entrepreneurship in Lesotho - Obiahu, Joseph Echem; Qutieshat, Abubaker (Rescollacom (Research Collaborations Community), 2024)
Entrepreneurship is acknowledged globally as a driver of unemployment reduction, poverty alleviation and national economic well-being. However, many nations, especially developing ones, struggle to sustain growth-oriented entrepreneurship due to limitations in their entrepreneurial ecosystems. With an unemployment rate of 28.9% as of 2019, Lesotho is one of the countries struggling to sustain effective entrepreneurial ecosystems. This article seeks to identify the inadequacies in local entrepreneurial ecosystems that impede the emergence of entrepreneurs and small-and-medium enterprises in Lesotho. This study, grounded in systems theory, utilised a qualitative approach using semi-structured interviews to collect data from twenty-five budding entrepreneurs. Data analysis showed that financial institutions funding, entrepreneurial apathy, poor infrastructure, dearth of talents and leaders, and inadequate support networks were the main barriers to entrepreneurship in Lesotho. This study raises awareness of Lesotho's entrepreneurial ecosystem's basic flaws, which hinder growth-oriented business. The study is expected to improve policymakers’ intervention strategies and attract more scholars' attention to the phenomenon. The study is limited in scope due to the participants' concentration in Maseru, the capital city. This geographical restriction is a limitation to the extent that businesses operating in the city and those operating in the countryside may experience different systemic impacts. Future research should explore broader scope.